The carbonate-hosted willemite prospects of the Zambezi Metamorphic Belt (Zambia) - Boni, Maria; Terracciano, Rosario; Balassone, Giuseppina; Gleeson, Sarah A.; Matthews, Alexander (Mineralium deposita, 2011)
Zambian willemite (Zn2SiO4) deposits occur in the metasedimentary carbonate rocks of the Proterozoic Katangan Supergroup. The most important orebodies are located around Kabwe and contain both sulphides and willemite in dolomites of low metamorphic grade. The Star Zinc and Excelsior prospects (Lusaka area), discovered in the early 1920s, occur in the metamorphic lithotypes of the late Proterozoic Zambezi Supracrustal sequence, which were deposited in a transtensional basin formed during the oblique collision of the Kalahari and Congo cratons. The deposits are hosted by the limestone and dolomitic marbles of the Cheta and Lusaka Formations. Structural analysis indicates that several fracture sets host the deposits, which may be genetically related to the Pan-African Mwembeshi dislocation zone (a major geotectonic boundary between the Lufilian Arc and the Zambezi Belt). In both prospects, willemite replaces the marbles and is found along joints and fissures with open-space filling textures and locally may develop colloform and vuggy fabrics as well. Silver as well as traces of germanium and cadmium have been detected within the willemite ore, and lead or zinc sulphides are scarce or absent. Calcite locally replaces willemite. Willemite is associated with specular hematite and franklinite and post-dates the Zn-spinel gahnite in the paragenesis. Genthelvite [Zn4Be3(SiO4)3S] occurs as a minor phase in irregular aggregates. The willemites from the Lusaka area, though Mn-poor, show green cathodoluminescence colours and bright green fluorescence in short-wave UV (as the high-temperature willemites in USA). Thermometric analyses of primary fluid inclusions in willemite yield homogenization temperatures that range from 160°C to 240°C and salinities of 8-16 wt.% equiv. NaCl. The homogenization temperatures suggest a hypogene-hydrothermal origin for the willemite concentrations. The geochemistry of fluid inclusion leachates suggests that the hydrothermal fluids were brines derived from highly evaporated seawater. Precise age constraints are currently lacking for the Lusaka area deposits, though the deposits are not deformed, indicating that they post-date the Lufilian orogeny (~520 Ma). The possibility of precursor ores exists; the gahnite-franklinite-willemite deposits could have been derived from a metamorphosed primary sulphide (or even nonsulphide) concentration that has subsequently been completely destroyed. However, there is no real evidence of such a primary source for the willemite mineral association. The Lusaka zinc ores may have been produced by an extensive hydrothermal system, with fluids discharging along basinal fracture zones controlled by the pre-Pan-African rifting stage. A paragenesis similar to that of the Lusaka prospects has been proposed to be a vector towards massive sulphide ores in several parts of the world; therefore, it is possible that these small willemite showings in Zambia may be part of a much bigger, and still unexplored, zinc province.